Pelatihan Pemanfaatan Sampah Plastik dan Keterampilan Membuat Souvenir dari Bahan Daur Ulang untuk Anak dan Remaja - Nurul Haniza; Amelia Naim Indrajaya (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON UTILIZATION OF PLASTIC WASTE AND SOUVENIR MAKING SKILLS FROM RECYCLED MATERIALS FOR CHILDREN AND YOUTH. Cempaka Putih Village is located in East Ciputat sub-district on the outskirts of Jakarta. In this kelurahan, there are still many children dropping out of school, high divorce rates, irregular parental work, which has an impact on juvenile delinquency. Therefore Cempaka Putih Village in East Ciputat District was chosen as a place of community service to target children and adolescents, in order to gain skills in making useful items from recycled materials such as plastic waste. We collaborate with PKBM (Community Learning Center) Lestari a nonprofit organization in the field of education and also with Eco Business Indonesia (EBI) an independent business that makes various kinds of goods from recycled materials. Community service activities are expected to provide sustainable benefits to the community of Cempaka Putih Village, especially in increasing business activities based on plastic waste-based recycling. In the medium term it is hoped that this program can build population independence in a sustainable manner both in economic, social and environmental terms. The program is also expected to be able to contribute in directing children and young people to be able to improve their abilities and fill their free time with useful activities. Long-term impacts are expected to generate income and have a positive effect to increase the creativity and innovation of children and adolescents. This achievement in Cempaka Putih Village can later be used as a model of community development in other Kelurahans so that superior products from each region emerge and develop.